Antipsychotics for Amphetamine Psychosis. A Systematic Review - Fluyau, Dimy; Mitra, Paroma; Lorthe, Kervens (Frontiers in Psychiatry, 2019)
Antipsychotics for amphetamine psychosis. A systematic review Abstract Background: Among individuals experiencing amphetamine psychosis, it may be difficult to rule out schizophrenia. The use of antipsychotics for the treatment of amphetamine psychosis is sparse due to possible side effects. Some arguments disfavor their use, stating that the psychotic episode is self-limited. Without treatment, some individuals may not fully recover from the psychosis and may develop full-blown psychosis, emotional, and cognitive disturbance. This review aims to investigate the clinical benefits and risks of antipsychotics for the treatment of amphetamine psychosis. Methods: Electronic search on trials on antipsychotic drugs for amphetamine psychosis from their inception to November 2018 was conducted in PubMed, Scopus, Google Scholar, EBSCOhost, ProQuest, Cochrane Review Database, Medline Ovid, and EMBASE following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. The Cochrane Risk of Bias Tool assessed the risk of bias, the methodological quality of individual trial was assessed by the Oxford Quality Scoring System, and the quality of evidence for recommendations was judged by the Grading of Recommendations, Assessment, Development, and Evaluations (GRADE). The results were synthesized qualitatively and quantitatively. Results: The investigation of six randomized controlled trials of 314 participants showed that aripiprazole, haloperidol, quetiapine, olanzapine, and risperidone were able to reduce or control the psychotic episode (positive and negative symptoms) induced by amphetamine use with no adverse event. Although the side effects profile of these agents varied, no drug was clinically superior to others. Conclusions: This review suggests that antipsychotics seem to be efficacious for amphetamine psychosis on both positive and negative symptoms. Practitioners need to tailor their use based on risks for side effect individually. Keywords: amphetamine psychosis, psychosis, and addictive disorders, treatment outcome, risk, amphetamine, and antipsychotics.